Pengaruh Sosialisasi Antisipatif, Keseriusan Kecurangan, dan Reward Terhadap Niat Whistleblowing dengan Moderasi Religiusitas - Ayuni Fransiska; Elok Heniwati; Angga Permadi Karpriana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The phenomenon of fraud in organizations, both in the public and private sectors, has significantly reduced public trust. One effective way to prevent and detect fraud is through whistleblowing. This study aims to analyze the effect of anticipatory socialization, seriousness of fraud, and rewards on whistleblowing intentions, with religiosity as a moderating variable. The research method used is a quantitative method with a survey approach. The sample in this study involved 121 students of the Tanjungpura University Accounting Study Program who had taken Auditing I and II courses. Data collection was carried out through distributing questionnaires online. The results showed that anticipatory socialization and the seriousness of fraud had a significant positive effect on whistleblowing intentions. However, providing rewards has no significant effect. Other findings show that religiosity is able to strengthen the effect of anticipatory socialization and seriousness of fraud on whistleblowing intentions, as well as strengthen the previously insignificant effect of rewards. These findings support the Theory of Planned Behavior, which states that behavioral intentions are determined by attitudes, subjective norms, and behavioral control.